Synthesis of Polyacrylamides from Derivatives 2-Aminobenzothiazole and also Preparation of Dibutylphthalate as a Plasticizer to Estimate Plasticization Behaviour for Prepared Polymers - Al-Tamimi, Entesar; Al-Lami, Naeemah Jabbar; Haasan, Waasan Jabbar (Al-Nahrain Journal of Science, 2018)
The present research involved preparation of heterocyclic polyacrylamides using reaction of polyacryloyl chloride with 2-aminobenzothiazole in the presence of a suitable solvent and amount of triethyl amine with heating. After that, Dibutylphthalate (DBP) has been used as a plasticizer for some prepared polymers, this plasticizer has shown a good behaviour toward change of softening point for these polymers, the optimal weight of DBP that must be added to polymer has been estimated by plotting between softening points of polymers with weight of DBP that added to polymers, the method used in this research can be applied to other polymers and other plasticizers to find optimal weight of plasticizer that give minimum softening points.